Take a bandana : 16 beautiful projects for your home - Schlee, Jemima (Guild of Master Craftsman Publications, 2015)
"This book features 16 fresh and contemporary sewing projects for the home and garden created with bandanas. All basic techniques and know-how are explained, with clear step-by-step instructions and pictures. It is part of a brand new series Take a...This attractive new title in the Take a...series presents 16 original projects for your home and garden created with bandanas. Available in an array of colours and patterns, the timeless bandana can create a striking design statement when upcycled and transformed into these eye-catching and practical makes. The projects fall into four main sections: Outside entertaining, In the workroom, In the Bedroom and Out and about. Anyone who is new to sewing need not worry. All the basic techniques and know-how are explained, with clear step-by-step instructions and pictures."--Boomerang Books website.